Sekolah Zero Bullying dengan Penguatan Pendidikan Karakter di SMK Nusa Persada Tengaran - Isfaizah; Risma Aliviani Putri; Ari Widyaningsih (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2023)
The rise of cases of violence that occur, especially at school age, makes parents and educators worry about their children's future. According to the Program for International Students Assessment (PISA) in Indonesia in 2018 as many as 41% of students had experienced bullying (bullying). In the same year, Indonesia was also in 5th position out of 78 countries with the most bullied students. This figure is truly ironic in the midst of the function of schools as a place to seek knowledge, develop one's potential and achievements, educate personal character, but instead they are used as a place to show off and bully their friends which causes the destruction of our generation. One way to prevent and create schools that have zero bullying is to strengthen character education among students. This community service aims to strengthen and increase students' knowledge about character education. This community service activity was held on March 7 2023 at Nusa Persada Tengaran Vocational School, which was attended by 46 class XI students with great enthusiasm. The methods used are lectures, discussions and character strengthening games. Activities given to strengthen the character of students is to provide strengthening of character education with character development material, forms of juvenile delinquency and bullying. Knowledge of students before being given health education about strengthening character education has a minimum value of 6 and a maximum of 9 and an average value of 7.75, and after being given health education there is an increase in adolescent knowledge about strengthening character education with an average score of 8.85, with a minimum score of 7 and a maximum of 10. This shows that this service activity is able to strengthen and increase students' knowledge about character education. It is hoped that activities that build the character of students like this can be carried out continuously to increase the positive character of students.   ABSTRAK                 Maraknya kasus kekerasan yang terjadi khususnya pada usia anak sekolah membuat kalangan orang tua dan para pendidik khawatir terhadap masa depan anak. Menurut Programme for Internasional Students Assesment (PISA) di Indonesia pada tahun 2018 sebanyak 41% siswa pernah mengalami perundungan (bullying). Di tahun yang sama, Indonesia juga berada pada posisi ke-5 dari 78 negara dengan murid yang mengalami perundungan paling banyak. Angka ini sungguh menjadi ironi di tengah fungsi sekolah sebagai tempat mencari ilmu, mengembangkan potensi dan prestasi seseorang, mendidik karaktek pribadi, namun dijadikan malah menjadi tempat ajang unjuk gigi dan membully temannya yang menyebabkan hancurnya generasi kita. Salah satu cara untuk mencegah dan mewujudkan sekolah yang zero bullying adalah dengan menguatkan pendidikan karakter di kalangan siswa/siswi. Pengabdian masyarakat ini bertujuan untuk menguatkan dan meningkatkan pengetahuan siswa/siswi tentang pendidikan karakter. Kegiatan pengabdian masyarakat ini pada tanggal 7 maret 2023 di SMK Nusa Persada Tengaran, yang diikuti oleh 46 siswa/siswi kelas XI dengan antusiasme yang tinggi. Metode yang digunakan adalah ceramah, diskusi dan game penguatan karakter. Kegiatan yang diberikan untuk menguatkan karakter siswa/siswi adalah dengan memberikan penguatan pendidikan karakter dengan materi pengembangan karakter, bentuk kenakalan remaja dan bullying.  Pengetahuan siswa/siswi sebelum diberikan pendidikan kesehatan tentang penguatan pendidikan karakter nilai minimal 6 dan maksimal 9 serta nilai rata-rata 7.75, dan setelah diberikan Pendidikan kesehatan terjadi peningkatan pengetahuan remaja tentang penguatan Pendidikan karakter dengan rata-rata nilai sebesar 8.85, dengan nilai minimal 7 dan maksimal 10. Hal ini menunjukkan bahwa kegiatan pengabdian ini mampu menguatkan dan meningkatan pengetahuan siswa/siswi tentang pendidikan karakter. Diharapkan kegiatan yang membangun karakter siswa/siswi seperti ini dapat dilakukan secara continue untuk meningkatkan karakter positif peserta didik.